Improving typography and minimising computation for documents with scalable layouts - Pinkney, Alexander J. (2015)
Since the 1980s, two paradigms have dominated the representation of formatted electronic documents: flowable and fixed. Flowable formats, such as HTML, EPUB, or those used by word processors, allow documents to scale to any arbitrary page size, but typographical compromises must be made since the layout is computed in real time, and is re-computed each time the document is displayed. Conversely, fixed formats such as SVG or PDF are afforded the potential for arbitrarily complex typography, but are constrained to the fixed layout that is set at the time of creation. With the recent surge in popularity of low-powered portable reading devices -- from tablets to e-readers to mobile phones -- there is an expectation that documents should scale to any size, maintain their high-quality typography, and not provide unnecessary strain on an already overloaded battery.